Effect of environmental and anthropogenic factors on the distribution and co-occurrence of cold-water corals - Palummo, Valeria; Milisenda, Giacomo; Canese, Simonepietro; Salvati, Eva; Pica, Daniela; Passarelli, Augusto; Spanò, Nunziacarla; Romeo, Teresa; Greco, Silvestro (Frontiers in Marine Science, 2023)
Cold-water corals (CWCs) are bioengineering species that can increase habitat heterogeneity and improve the deep sea's biological diversity and ecosystem functioning. Knowledge of their distribution provides a critical baseline for assessing the effect of natural and anthropogenic impacts on these important deep-sea habitats. The aims of this study are: i) provide new data on the spatial distribution of six CWCs species in the Strait of Sicily, ii) describe the principal environmental and anthropogenic variables that play a role in shaping their distribution, iii) identify hotspots in which individuals belonging to the various species co-occur. Presence-only data of six CWCs species, ten environmental variables (depth, slope, rugosity, aspect, flowdir, temperature, salinity, North bottom current, East bottom current, chlorophyll-a), and one variable relating to bottom trawling effort (Automatic Information System -AIS) were used to predict the suitable habitats. We used Maximum Entropy modelling (MaxEnt) approach and used the AUC (area under the receiver operating characteristic curve) and TSS (true skill statistics) to evaluate the model performance. The results showed excellent AUC, TSS and AUC's standard deviation mean values for all six species. The validation shows high predictive performance. MaxEnt identified slope, depth, and rugosity as the most important predictors, showing the highest percentage contribution for all six species considered. Throughout the study area, highly interspecific persistent density hotspot of CWC co-occurrence were hypothesized, with a total extension of 4.05 km 2 where all species could co-occur. Although studies on the effect of environmental and anthropogenic factors that impact the distribution of these species of conservation 2 This is a provisional file, not the final typeset article interest remain scarce, the results of this study offer useful guidance for decision-makers to develop necessary conservation measures.